Characteristics of aerosol size distribution and liquid water content under ambient RH conditions in Beijing. (15th December 2022) - Dai, Haosheng; Zhang, Jiaoshi; Gui, Huaqiao; Shen, Lin; Wei, Xiuli; Xie, Zhibo; Chen, Shiyi; Wu, Zhijun; Chen, Da-Ren; Liu, Jianguo
Abstract: The variation of ambient relative humidity (RH) affects the water uptake of aerosols in the atmosphere, thereby altering the aerosol size distribution and mass concentration. In this study, aerosol size distributions under both dry and ambient RH conditions are measured using an active RH-controlled dry-ambient aerosol size spectrometer (DAASS) at an urban site in Beijing during the springtime of 2021, and the aerosol liquid water content (ALWC) is derived accordingly. During the measurement period, a sharp increase of the ALWC was commonly observed when ambient RHs reached above 50%, demonstrating a potential phase change of the aerosol which further increases the rate of water uptake. Considerably high ALWC events were observed during the nighttime, with further elevated ambient RH above 60%. The liquid water accounts for up to 42.5% of the total aerosol volume, corresponding to a maximum ALWC of 8.79 μg m −3 . The evolution of geometric mean diameter of accumulation mode particles agrees well with the enhancement of the ALWC (R 2 of 0.73), revealing a significant growth of accumulation mode particles resulting from water uptake. Besides, by investigating the RH-dependent ambient aerosol surface area concentration, it is found that the aerosol surface area concentration can be underestimated by ∼20% under dry conditions when the ambient RH elevates to above 70%. Highlights: Sharp increases of the ALWC were observed under ambient RHs above 50% during the nighttime. The aerosol water uptakes are represented by a significant growth of accumulation mode particles. The aerosol surface area concentration can be underestimated under dry conditions when the ambient RH elevates to above 70%.